Huperzine A: Is it an Effective Disease-Modifying Drug for Alzheimer’s Disease? - Qian, Zhong Ming; Ke, Ya (Frontiers in Aging Neuroscience, 2014)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder for which there is no cure. Huperzine A (HupA) is a natural inhibitor of acetylcholinesterase (AChE) derived from the Chinese folk medicine Huperzia serrata (Qian Ceng Ta). It is a licensed anti-AD drug in China and is available as a nutraceutical in the US. A growing body of evidence has demonstrated that HupA has multifaceted pharmacological effects. In addition to the symptomatic, cognitive-enhancing effect via inhibition of AChE, a number of recent studies have reported that this drug has “non-cholinergic” effects on AD. Most important among these is the protective effect of HupA on neurons against amyloid beta-induced oxidative injury and mitochondrial dysfunction as well as via the up-regulation of nerve growth factor and antagonizing N-methyl-D-aspartate receptors. The most recent discovery that HupA may reduce brain iron accumulation lends further support to the argument that HupA could serve as a potential disease-modifying agent for AD and also other neurodegenerative disorders by significantly slowing down the course of neuronal death.